2018
DOI: 10.3390/vaccines6030064
|View full text |Cite|
|
Sign up to set email alerts
|

A Universal Influenza Virus Vaccine Candidate Tested in a Pig Vaccination-Infection Model in the Presence of Maternal Antibodies

Abstract: The antigenically conserved hemagglutinin stalk region is a target for universal influenza virus vaccines since antibodies against it can provide broad protection against influenza viruses of different subtypes. We tested a universal influenza virus vaccination regimen based on sequential immunization with chimeric hemagglutinin (HA) containing viruses in a swine influenza virus pig model with maternal antibodies against pandemic H1N1. Vaccines were administered as live attenuated virus or inactivated influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…VAERD could be reversed when the NA was matched in the vaccine and challenge strain (57) or dampened when M2 protein was administered in conjunction with the respective WIV (58) suggesting that there is an interplay between antibodies targeting different components of the virus. However, the etiology of VAERD remains controversial as a recent paper showed that induction of VAERD by immunization with an adjuvanted H1N2 vaccine, followed by challenge with pandemic H1N1, did not correlate with the presence of anti-stalk antibodies (59).…”
Section: Antibody Mediated Protection Against Swiav Infectionmentioning
confidence: 99%
“…VAERD could be reversed when the NA was matched in the vaccine and challenge strain (57) or dampened when M2 protein was administered in conjunction with the respective WIV (58) suggesting that there is an interplay between antibodies targeting different components of the virus. However, the etiology of VAERD remains controversial as a recent paper showed that induction of VAERD by immunization with an adjuvanted H1N2 vaccine, followed by challenge with pandemic H1N1, did not correlate with the presence of anti-stalk antibodies (59).…”
Section: Antibody Mediated Protection Against Swiav Infectionmentioning
confidence: 99%
“…At the same time, many experiments redirecting the immune response to the conserved part of HA by modulation of the immunization protocols were described (Hai et al, 2012;Krammer and Palese, 2014;Sunwoo et al, 2018). Multiple immunizations with chi-meric molecules composed of the stem of one HA subtype and a globular part of different subtypes redirected the antibody response to the repeatedly presented conserved HA2-stem.…”
Section: Strategies Of the Development Of New Ha2-based Anti-influenzmentioning
confidence: 99%
“…Currently, two types of influenza vaccines containing IAV of H1 and H3 subtypes and one or two influenza B virus antigens are approved in human medicine. These are live attenuated vaccines, permitted only in USA and Russia, or inactivated vaccines Sunwoo et al, 2018). The most commonly used inactivated vaccines are split virus vaccines and subunit vaccines containing purified surface glycoproteins of virus (Stropkovská et al, 2010;Soema et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to antibodies, other bioactive molecules are found in breast milk, including cytokines and human milk oligosaccharides (HMOs) that have been shown to inhibit viral entry into cells [189][190][191]. Furthermore, cells are transferred to the infant via breastfeeding, which could play a role in shaping the neonatal and infant microbiome [192].…”
Section: A Key Role For Maternal Vaccination In Protecting Young Infamentioning
confidence: 99%